HARASSMENT AGAINST WOMEN IN THE WORKPLACE - Bertacini, Paula Fernanda; Paulucci, Tamiris Sousa; de Oliveira, Mara Janaina Gomes (Revista Interface Tecnológica, 2023)
Nowadays, women have been standing out in the market and conquering more and more space in the corporate world. However, they are the biggest victims of moral and psychological harassment in the workplace, which, most of the time, does not have an adequate internal structure to support the victims or punishments compatible with each type of harassment committed. This paper aims to analyze the types of recurrent harassment against women who work in the commercial and industrial areas in the city of São Carlos, presenting the physical and psychological consequences after the facts; the reaction of the victims through denunciation, and if there was company action for the due punishment of the culprits. The methodology was carried out through a questionnaire applied to 116 women. In the sample, it was found that most of the women who experienced moral and psychological harassment were married, and with higher education. They did not report it for fear of being fired, and as a consequence, they had mood swings and increased anxiety, besides emphasizing that the companies they worked for did not have a reporting channel.